STRATEGI PONDOK PESANTREN AAYAATUR RAHMAN CERME GRESIK DALAM MENINGKATKAN HAFALAN QUR’AN - El-Yunusi, Muhammad Yusron Maulana; Masduqoh , Dzurrotul (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LP2M) UIN Datokarama Palu, 2023)
This research aims to determine the strategy of the Aayaatur Rahman Cerme Gresik Islamic boarding school in improving memorization of the Qur'an in the millennium era. This research is qualitative research using a phenomenological approach. The object of research is students at the Aayaatur Rahman Cerme Gresik Qur'an Islamic Boarding School. Data collection uses interviews, observation, and documentation. Data analysis uses reduction, display, and triangulation. The results of the research are the strategies of the Talaqqi, Takrir, Tulis, Tasmi' and Tarjim methods. The implementation goes through three stages, namely preliminary activities (pre-method), core activities, and closing activities. The supporting factors are personal factors, such as the existence of strong intentions, interests, physical, and mental health in students; then the teacher factor, who gives rewards/gifts to the students, and synergizes with the students' guardians; as well as parental and family factors (creating an environment of love for the Koran, adequate nutrition, implementing a clean, safe, child-friendly and religious environment); and learning/Islamic boarding school environment factors (support from teachers and homeroom teachers, good learning methods, there is a schedule/memorization target and using one mushaf when memorizing). The inhibiting factors in implementing this method are firstly the character, intelligence, and age of the students; then the memorization target schedule changes; Furthermore, cooperation between teachers and guardians of students is lacking; as limited classroom space and teacher human resources; The last thing is that students often take permission so they cannot read the Koran fluently and are not muqim